Site-specific conjugation of 8-ethynyl-BODIPY to a protein by [2 + 3] cycloaddition1. Issue 24 (28th June 2015) - Albrecht, Marcel; Lippach, Andreas; Exner, Matthias P.; Jerbi, Jihene; Springborg, Michael; Budisa, Nediljko; Wenz, Gerhard
<x xml:space="preserve">Abstract</x> We report a straightforward synthesis of 8-ethynyl-BODIPY derivatives and their potential as fluorescent labeling compounds using an alkyne–azide click chemistry approach.